PSYCHOSOCIAL REHABILITATION OF WOMEN AFFECTED BY INSURGENCY IN BORNO STATE, NIGERIA: AN EVALUATION OF SUPPORT PROGRAMS - Egbujiobi, Anthonia Efe (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2025)
The purpose of this research is to evaluate the effectiveness of the skill-building and psychosocial support programs utilized in Borno State to rehabilitate women affected by the violent Boko Haram conflict. The conflict in Borno State has caused widespread displacement, fatalities, sexual assault, kidnappings and severe damage to infrastructure, property and livelihood. Women have been subjected to violence based on their gender, and made to face various vices including forced marriages, sexual servitude and other serious abuses of their human rights. As a result of their ordeal, women suffered significant psychological consequences in the Boko Haram conflict, leading to post-traumatic stress disorders (PTSD), anxiety, sadness and social stigma. Using qualitative data and the content analysis approach with emphasis on secondary sources, this paper evaluated the effectiveness of stakeholders’ responses to the plight of women affected by the insurgency in Borno state through psychosocial and skills acquisition programs. It found a correlation between psychosocial therapies and assimilation of skills-building programs in the affected women in Borno state on the one hand, and on the other hand, it found that the psychosocial and skills-acquisition programs have positively impacted on the lives of these women improving their social ties, trauma symptoms and economic self-sufficiency. Although, the paper observed various challenges militating against the effectiveness of these programs, it concluded that the psychosocial and skill-acquisition programs adopted in Borno state have been quite effective, and can be improved with more investment, financing and commitment.